PROJECTED ROTATIONAL VELOCITIES AND STELLAR CHARACTERIZATION OF 350 B STARS IN THE NEARBY GALACTIC DISK - Bragança, G. A.; Daflon, S.; Cunha, K.; Bensby, T.; Oey, M. S.; Walth, G. (The Astronomical journal, 2012)
Projected rotational velocities (v sin i) are presented for a sample of 350 early B-type main-sequence stars in the nearby Galactic disk. Spectral types were estimated based on relative intensities of some key line absorption ratios and comparisons to synthetic spectra. Effective temperatures were estimated from the reddening-free Q index, and projected rotational velocities were then determined via interpolation on a published grid that correlates the synthetic FWHM of the He I lines at 4026, 4388 and 4471A with v sin i. The v sin i distribution obtained for the entire sample is found to be essentially flat for v sin i values between 0 and 150 km s super(-l), with only a modest peak at low projected rotational velocities. Furthermore, for a subsample of potential runaway stars we find that the v sin i distribution resembles the distribution seen in denser environments, which could suggest that these runaway stars have been subject to dynamical ejection mechanisms.